Rhizobium pusense associated to chickpea (Cicer arietinum L.), in Cuba - Ortega-García, Marisel (2024)
Introduction. Chickpea has been considered a restricted host species for nodulation, although recent studies describe a greater bacterial diversity associated with the crop to increase the knowledge about this symbiosis in orden to obtain efficient isolates in its contribution. Objective. To characterize and identify an isolate obtained from chickpea plant nodules and evaluate its effectiveness under field conditions. Materials and methods. The research was conducted in the laboratories of two centers: the Institute of Fundamental Research in Tropical Agriculture “Alejandro de Humboldt,” Cuba, and the National Center for Genetic Resources, Mexico, as well as under field conditions in two campaigns during the years 2018 and 2020 to demonstrate its effectiveness in crop interaction in the first center. The isolate R3 was taxonomically identified through the sequencing of four genes. For laboratory experiments, a completely randomized design was used, while plant trials were conducted under a randomized block design. The results were subjected to analysis of variance, and means were compared using the Tukey test (p<0.05). Results. The isolate R3 showed variability in terms of its morpho-physiological and biochemical characteristics. Furthermore, it exhibited significant differences compared to the other treatments in the growth and yield indicators evaluated in chickpea. Conclusions. Rhizobium pusense associated with chickpea nodules was identified for the first time in Cuba. The strain demonstrates growth at pH levels between 5.5 and 9.0 and temperature ranges from 29 °C to 38 °C, indicating its tolerance to these factors. Its inoculation in chickpea stimulates nodule formation and increased yield-related variables.